2020
DOI: 10.3390/ani10091660
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Handheld Near-Infrared Spectrometer to Predict Gelatinized Starch, Fiber Fractions, and Mineral Content of Ground and Intact Extruded Dry Dog Food

Abstract: The aim of the present study was to investigate the ability of a handheld near-infrared spectrometer to predict total and gelatinized starch, insoluble fibrous fractions, and mineral content in extruded dry dog food. Intact and ground samples were compared to determine if the homogenization could improve the prediction performance of the instrument. Reference analyses were performed on 81 samples for starch and 99 for neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
(64 reference statements)
2
8
2
1
Order By: Relevance
“…The average was 1.02 g per 100 g DM with the range 0.38-1.53 g per 100 g DM. Our results were lower than in Goi et al [2020b] results, where the average level of ADL was 1.85 g per 100 g DM, with the range 0.43-4.58 g per 100 g DM.…”
Section: Dietary Fiber Fractionscontrasting
confidence: 95%
See 1 more Smart Citation
“…The average was 1.02 g per 100 g DM with the range 0.38-1.53 g per 100 g DM. Our results were lower than in Goi et al [2020b] results, where the average level of ADL was 1.85 g per 100 g DM, with the range 0.43-4.58 g per 100 g DM.…”
Section: Dietary Fiber Fractionscontrasting
confidence: 95%
“…The results obtained in this study were higher than those reported by de-Oliveira et al [2012] who report the NDF range in dog feed 6.5-11.7 g per 100 g DM. On the other hand, Goi et al [2020b] obtained results in the study of extruded dog food similar to the presented study (mean 16% NDF).…”
Section: Dietary Fiber Fractionssupporting
confidence: 88%
“…Los valores de almidón no presentaron diferencia significativa entre laboratorios, pero se aprecia una diferencia importante (p=1.28E -09 ) entre alimentos (32.3, 37.73 y 26.37% para A1, A2 y A3, respectivamente). Los niveles de inclusión del almidón son manipulados por los fabricantes de alimentos balanceados extruidos para expandir las croquetas a fin de obtener una textura más apropiada (Goi et al, 2020). No obstante, el almidón en exceso puede provocar intolerancia alimentaria, produciendo atrofia de las vellosidades intestinales, lo que induce a presentación de diarrea causada por una mala absorción (Grandjean y Butterwick, 2009).…”
Section: Discussionunclassified
“…The remaining 42 samples were used for external validation of the prediction models [41]. Samples were selected according to Mahalanobis distance H [42]. Additionally, cross-validation was used to test the accuracy of the calibration in each step.…”
Section: Spectral Preprocessing and Calibration Models Developmentmentioning
confidence: 99%